Digital Creativity Development in an E-learning Environment – A 3D Design Project - Klima, Gábor; Kárpáti, Andrea (Central European Journal of Educational Research, 2021)
During the pandemic, arts disciplines had to seek new paths for creation to continue visual skills development outside the studio. ICTs offer a natural tool set for individual and collaborative work and sharing online. 3D design and the development of digital creativity can represent new directions for Hungarian art education and its major discipline called Visual Culture. With this tool, visual art education can proceed on the bumpy road to teach the visual language of the 21st century. Certainly, technological focus is not the only option for progress in art education. Nevertheless, if we look for possible directions for renewal, we cannot ignore the use of software products that support visual creativity,and are becoming more and more easily available, simpler and free of charge. This paper focuses on the pedagogical possibilities of 3D printing. We present an experimental program with secondary school students aged 16 years, that started and ended face-to-face and was partly realised online. As the project manifests a creative synergy of Visual Culture and Information Technology disciplines that may be of interest for art and ICT educators as well.